Estimation of Fish Production from Hirakud Reservoir - VARGHESE, M D; NAIR, A.K KESAVAN; GEORGE, V C; KHAN, A A (Fishery Technology, 2017)
A suitable procedure based broadly on stratified random sampling for estimation of fish production from H.irakud reservoids described. The total fish productwn for the years 1978 and 1979 from Hirakud reservoir, along with seasonal variation of different species is discussed.